2020
DOI: 10.22452/ijie.vol13no2.4
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Customers’ Behavioural Intention towards Islamic Microfinance Services in Bangladesh

Abstract: The present study investigates the behavioural intention of prospective customers towards Islamic microfinance services in Bangladesh based on demographic factors such as gender, age, education, and family size. This study uses a self-administered survey questionnaire to determine the intention of prospective customers towards Islamic microfinance services based on five variables, namely subjective norms, attitude towards behaviour, behavioural intention, normative belief, and behavioural belief. A total of 45… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 31 publications
(41 reference statements)
0
6
0
Order By: Relevance
“…Significantly, scholarly research in the field of Islamic finance has placed considerable emphasis on the significance of attitude as a crucial determinant in shaping the intention to utilize Islamic personal financing, as highlighted by Amin et al (2010). Moreover, previous research has indicated that individuals with a positive attitude or a favorable inclination toward Islamic financing exhibit a greater intention to obtain Islamic personal financing products (Fauziah et al, 2008;Ahmed et al, 2021). Jaffar and Musa (2016) examined the inclination of non-user business owners to utilize Islamic financing.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Significantly, scholarly research in the field of Islamic finance has placed considerable emphasis on the significance of attitude as a crucial determinant in shaping the intention to utilize Islamic personal financing, as highlighted by Amin et al (2010). Moreover, previous research has indicated that individuals with a positive attitude or a favorable inclination toward Islamic financing exhibit a greater intention to obtain Islamic personal financing products (Fauziah et al, 2008;Ahmed et al, 2021). Jaffar and Musa (2016) examined the inclination of non-user business owners to utilize Islamic financing.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Previous studies also recommend that competence is a vital factor for establishing organizational performance and employee performance in an organization. On top of it, according to the needed performance standards, competence is http://dx.doi.org/10.21511/bbs.18 (2).2023.11 defined as a set of skills and knowledge and the ability to use these skills and knowledge in a job or company or across industries, which is divided into two parts, for example, technical competence (level of education, ability to analyze, and work experience) and non-technical competence (attitude, flexibility, self-confidence, and self-control have a direct impact on employee performance (Swanson et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…But workers are seen as the company's biggest asset (Bedarkar & Pandita, 2014), human resource management is crucial because it provides leadership and guidance to the organization's human resources (Ai et al, 2022;Bashir & Ramay, 2008). Nowadays, banking organizations referred to as the economy's vital organs which is the key indicator of the economy of a nation (Jahan et http://dx.doi.org/10.21511/bbs.18 (2).2023.11 al., 2020; Ahmed et al, 2021). The banking sector is growing rapidly in Bangladesh Islam & Bhuiyan, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Widyastuti et al, 2022 conducted research on the intention to invest in the Islamic capital market. Maulana, 2018;Ahmed, 2021;Mansori, 2020;Umar, 2021 have conducted research on the intention to use Islamic financial institution products.…”
Section: Introductionmentioning
confidence: 99%